Owning the masters a history of sound recording copyright - Osborne, Richard 1967- (New York Bloomsbury Academic, a trademark of Bloomsbury Publishing Plc, 2023)
"The story of how record companies gained ownership of sound recording rights and examines the consequences of this ownership for musical creation and reception"--Provided by publisher.
Mechanizing -- Performing -- Producing -- Expanding -- Justifying -- Networking -- Owning.
Includes bibliographical references and index.
Keywords: Sound recording industry -- History; Copyright -- Sound recordings -- History; Copyright -- Music -- History